PENAMPILAN KARAKTER HASIL EMPAT VARIETAS PADI MELALUI SISTEM TANAM JAJAR LEGOWO 2:1 DI DESA TINCEP KABUPATEN MINAHASA - Marina F. Rumagit; Arthur Pinaria; Wenny Tilaar (COCOS, 2017)
ABSTRACTThe purpose of this study was to determine performance of the four rice varieties based on yield characters at Tincep village, Minahasa regency. The research was conducted in the Tincep Village, District of Sonder, Minahasa regency from June to October 2016. The experimental designed was used Randomized Block Design (RBD). The treatment were fout rice varieties namely Ciherang (P1), Mekongga (P2), Cigeulis (P3), and Suluttan Unsrat 2 (P4). Each treatment was replicated three times. The results showed that the treatment of the four varieties were not different base on observed characters viz weight of 1000 grain, harvest grain weight , number of unfilled grain, grain dry weight, and number of filled grain.Keywords : Varieties rice, yield characters, jajar legowo